Pengembangan dan Implementasi LMS untuk Pengembangan Karir dan Beasiswa Bagi Alumni Serta Peserta Didik Prasejahtera - Ariq Cahya Wardhana; Irmayatul Hikmah; Arif Amrulloh; Yudha Islami Sulistya; Christian Felix Saliman Sugiono; Yoga Eka Pratama (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to improve access to career and scholarship information for alumni and underprivileged students at SMK Maarif NU 1 Purwokerto through the development and implementation of the Learning Management System (LMS). This LMS is designed as a digital platform that provides job vacancy information, skills training, and scholarship opportunities, supported by interactive features that are easily accessible through a Flutter-based mobile application and API integration from Moodle. The development process is carried out through five stages, namely identification of needs, system development, program implementation, monitoring and evaluation, and sustainability planning. The results of the usability test showed a score of 79.88 with a grade A, indicating that the system has a high level of ease of use. This program not only provides applicable technological solutions, but also strengthens students' readiness to face the world of work and further education independently and sustainably